Pengaruh Strategi Bisnis terhadap Kinerja Manajemen Operasional Perusahaan di Kota Medan - Merry Moy Mita; Siagian, Supriadi; Rila Maufira; Muridha Hasan (MAMEN: Jurnal Manajemen, 2025)
This study aims to analyze the influence of business strategy on the operational management performance of companies. In an increasingly competitive global business environment, companies are required to manage resources effectively and efficiently to achieve sustainable competitive advantage. Strong operational management is a key factor for companies to meet customer needs, reduce production costs, and improve productivity and service quality. This study adopts a quantitative approach with a causal method to examine the relationship between business strategy and operational management variables. The sample consists of 102 respondents selected from two companies in Medan City using purposive sampling. Data were collected through a closed-ended Likert-scale questionnaire and supporting company documentation. The results of data analysis indicate that business strategy has a significant influence on operational management performance, as evidenced by the results of the F-test and T-test. A well-designed and integrated strategy can improve production process efficiency, service quality, and customer satisfaction. This study provides a theoretical contribution by enriching the literature on strategic and operational management, as well as practical implications by assisting companies in formulating more adaptive business strategies in response to external environmental changes. These findings may also serve as a foundation for managerial decision-making aimed at enhancing corporate competitiveness.